2019
DOI: 10.1519/jpt.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Validity, and Ability to Identity Fall Status of the Berg Balance Scale, Balance Evaluation Systems Test (BESTest), Mini-BESTest, and Brief-BESTest in Older Adults Who Live in Nursing Homes

Abstract: Background and Purpose: In any given year, 28% to 35% of older adults experience falls. In nursing home environments, the annual rate of falls increases to 30% to 50%. Our objective was to verify and compare the reliability, validity, and ability to identify falls of the Berg Balance Scale (BBS), Balance Evaluation Systems Test (BESTest), Mini-BESTest, and Brief-BESTest for older adults who live in nursing homes. Methods: This was a cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 54 publications
0
51
2
1
Order By: Relevance
“…Além disso, segundo Viveiro et. al 32 pontuações menores que 47 na EEB em idosos institucionalizados indicam um maior risco de quedas. Apesar do GE não apresentar uma mudança significativa após a intervenção, nota-se que ambos os grupos GE e GC apresentaram pontuações acima de 47, portanto um baixo risco de quedas.…”
Section: Discussionunclassified
“…Além disso, segundo Viveiro et. al 32 pontuações menores que 47 na EEB em idosos institucionalizados indicam um maior risco de quedas. Apesar do GE não apresentar uma mudança significativa após a intervenção, nota-se que ambos os grupos GE e GC apresentaram pontuações acima de 47, portanto um baixo risco de quedas.…”
Section: Discussionunclassified
“…In addition, an MCID of 3 points has been produced for the BBS in individuals with multiple sclerosis, 7 points in individuals with neurological disorders, and 3.5 to 7.1 points in individuals with chronic obstructive pulmonary disease . Other work has established the minimal detectable change (MDC) for the various versions of the BESTest and BBS, and found greater values for the Mini‐BESTest and Brief‐BESTest than the MCID estimates calculated in the current study . There are several reasons for the difference in findings.…”
Section: Discussionmentioning
confidence: 53%
“…36 Other work has established the minimal detectable change (MDC) for the various versions of the BESTest and BBS, and found greater values for the Mini-BESTest and Brief-BESTest than the MCID estimates calculated in the current study. 39,40 There are several reasons for the difference in findings. First, their studies measured MDC, which represents a minimal change required to distinguish a real performance change from a change due to measurement error or variability in performance with repeated testing.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of normative values in outcome measures for older adults living in RAC as most work to date has been on healthy older adults living in the community [ 54 ]. An example of this is of the outcome measures used in this study only three have had a minimal detectable change identified: MoCA 4 points [ 36 ]; Brief BESTest 4 points [ 55 ]; SPPB total 1 point [ 56 ]; however, only the Brief BESTest established this for a population of older adults living in RAC. Consideration should be given to this when selecting measures for future studies.…”
Section: Discussionmentioning
confidence: 99%